Time From Human Immunodeficiency Virus Seroconversion to Reaching CD4+ Cell Count Thresholds <200, <350, and <500 Cells/mm3: Assessment of Need Following Changes in Treatment Guidelines - Lodi, Sara; Phillips, Andrew; Touloumi, Giota; Geskus, Ronald; Meyer, Laurence; Thiébaut, Rodolphe; Pantazis, Nikos; del Amo, Julia; Johnson, Anne M.; Babiker, Abdel; Porter, Kholoud (Clinical infectious diseases, 2011)
Background. Recent updates of human immunodeficiency virus (HIV) treatment guidelines have raised the CD4+ cell count thresholds for antiretroviral therapy initiation from 350 to 500 cells/mm 3 in the United States and from 200 to 350 cells/mm 3 in mid- and low-income countries. Robust data of time from HIV seroconversion to CD4+ cell counts of 200, 350, and 500 cells/mm 3 are lacking but are needed to inform health care planners of the likely impact and cost effectiveness of these and possible future changes in CD4+ cell count initiation threshold. Methods. Using Concerted Action on Seroconversion to AIDS and Death in Europe data from individuals with well-estimated dates of HIV seroconversion, we fitted mixed models on the square root of CD4+ cell counts measured before combined antiretroviral therapy (cART) initiation. Restricting analyses to adults (age >16 years), we predicted time between seroconversion and CD4+ cell count <200, <350, and <500 cells/mm 3 as well as CD4+ cell count distribution and proportions reaching these thresholds at 1, 2, and 5 years after seroconversion. Results. Median (interquartile range [IQR]) follow-up for the 18 495 eligible individuals from seroconversion while cART-free was 3.7 years (1.5, 7). Most of the subjects were male (78%), had a median age at seroconversion of 30 years (IQR, 25—37 years), and were infected through sex between men (55%). Estimated median times (95% confidence interval [CI]) from seroconversion to CD4+ cell count <500, <350, and <200 cells/mm 3 were 1.19 (95% CI, 1.12—1.26), 4.19 (95% CI, 4.09—4.28), and 7.93 (95% CI, 7.76—8.09) years, respectively. Almost half of infected individuals would require treatment within 1 year of seroconversion for guidelines recommending its initiation at 500 cells/mm 3 , compared with 26% and 9% for guidelines recommending initiation at 350 and 200 cells/mm 3 , respectively. Conclusions. These data suggest substantial increases in the number of individuals who require treatment and call for early HIV testing.